Pengaruh Pupuk N, P, K dan Pupuk Nano Silika Terhadap N-total, Serapan N dan Hasil Padi Hitam (Oryza sativa L. indica) pada Inceptisols - Anni Yuniarti; Islamy Hasan Hermawan; Rija Sudirja; Dirga Sapta Sara (Fakultas Pertanian Universitas Padjadjaran, 2021)
The Inceptisols have the potential to be developed into rice cultivation land because it is widely distributed in Indonesia but it has a low of soil fertility. Fertilization of N, P, K and Nano Silica fertilizers are efforts to provide nutrients for rice plants. Black rice that functional cultivated is Bangir Lokal Cianjur Variety. This study aims to determine the effect of N, P, K and Nano Silica fertilizes on total N content, N uptake, and Black Rice Yield (Oryza sativa L. indica) on Inceptisols. This research was conducted in November 2020 until March 2021 at the Soil Chemistry and Plant Nutrition Experimental Field, Faculty of Agriculture, Universitas Padjadjaran. Jatinangor with altitude 723 m asl. The experimental design was carried out using a RBD consisting of eight treatments and four replications. The treatments consisted of control ( without fertilizers); 1 N, P, K (Urea 300 kg/ha, SP-36 50kg/ha, and KCl 50 kg/ha);1 N, P ,K + 1 Nano Silica (2 mL/L); 1 N, P, K + 1,5 Nano Silica (3 mL/L); 1 N, P ,K + 2 Nano Silica (4 mL/L); ¾ N, P, K (Urea 225 kg/ha, SP-36 37,5kg/ha, and KCl 37,5 kg/ha) + 1 Nano Silica; ¾ N, P, K + 1,5 Nano Silica; ¾ N, P, K + 2 Nano Silca. The result showed that the combination of fertilizers doses of 1 N, P, K and 1 Nano Silica gives the best black rice yield with Dry Grain weight of 77,8 g/clump of rice